REDESAIN INTERIOR SEAWORLD, TEATER 4 DIMENSI TAMAN FESTIVAL BALI DI DENPASAR - Ananda Nur Sukarno; I Gusti Agung Haryawan; Nyoman Ratih Prajnyani Salain (Jurnal PATRA, 2019)
Tourist area is one of the potential to be developed and managed maximally which is directly related to the community. Tourism area development is generally followed by various efforts carried out, for example, revitalization & redesign. Revitalsasi is building the infrastructure and manage the functions of a place as a tourist destination at the same time a means of recreation for families. The island of Bali has a lot of beauty to be enjoyed by tourists. One is the Padang Galak Beach in Denpasar. Padang Galak Beach has a Festival Park that will be managed like Ancol beach in Jakarta which is equipped with entertainment rides. But in 2000 there was an Asian economic crisis so that the Taman Festival Bali went bankrupt. The government should pay attention to the existence of Taman Festival Bali tourism objects whose conditions need to be redesigned.To reduce the destroyed buildings, it is expected that with the development and revitalization of the Taman Festival Bali, it can be useful to increase the attractiveness of the Bali Garden Festival in the eyes of tourists. Some things in the Taman Festival Bali need addressed both in terms of facilities, the addition of rides, attractions, Sea World Theater 4 dimensions, as well as the comfort of the interior be primary points to revive the Taman Festival Bali. The design method used through some hangovers, namely: Object Identification; Problem Identification Phase; Method of collecting data; Analysis and Design Methods; and Design Methods. The concept applied at Taman Festival Bali is a combination of shades of coastal concepts that aim to solve the problems that exist in this design object.